2011
DOI: 10.1007/s10236-011-0508-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of meteorological climate models as inputs for coastal studies

Abstract: Modeling studies of future changes in coastal hydrodynamics, in terms of storm surges and wave climate, need appropriate wind and atmospheric forcings, a necessary requirement for the realistic reproduction of the statistics and the resolution of small scale features. This work compares meteorological results from different climate models in the Mediterranean area, with a focus on the Adriatic Sea, in order to assess their capability to reproduce coastal meteorological features and their possibility to be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…The adopted COSMO-CLM wind products were analyzed and assessed in the work of Bellafiore et al (2012), where wind fields resulting from different regional climate models were compared versus observations collected at four different wind stations in the Adriatic Sea area. The results presented showed that C14E5 dataset was the best performing among five different datasets in reproducing the mean and extreme wind conditions in the Adriatic Sea, even if the tendency to underestimate Bora winds was shown.…”
Section: Meteorological Cosmo-clm Modelmentioning
confidence: 99%
“…The adopted COSMO-CLM wind products were analyzed and assessed in the work of Bellafiore et al (2012), where wind fields resulting from different regional climate models were compared versus observations collected at four different wind stations in the Adriatic Sea area. The results presented showed that C14E5 dataset was the best performing among five different datasets in reproducing the mean and extreme wind conditions in the Adriatic Sea, even if the tendency to underestimate Bora winds was shown.…”
Section: Meteorological Cosmo-clm Modelmentioning
confidence: 99%
“…In addition, climate change induced effects at global or regional scales have not been yet completely understood, and as a consequence there is a large uncertainty on the effects that they may have on coastal zones [2].…”
Section: Introductionmentioning
confidence: 99%
“…This is an indication that the problem is in the correct prediction of the bora-easterly winds. This problem has been recently discussed from the meteorological point of view in Bellafiore et al (2012) for the northern Adriatic Sea. In view of the complex orography of the area, given that the operational BOLAM runs at 0.1…”
Section: Ortonamentioning
confidence: 99%
“…The two main problems with surface wind forecast are the parametrisation of the boundary layer processes and the spatial resolution of the meteorological model. There are many studies in literature (for Mediterranean Sea see, e.g., Signell et al, 2005;Bertotti et al, 2006Bertotti et al, , 2009Cavaleri and Bertotti, 2003;Cavaleri and Sclavo, 2006;Bellafiore et al, 2012) indicating that the use of meteorological hydrostatic limited area models (LAM) can effectively improve wave forecast at regional scale, in particular where the the topography affects significantly the mesoscale flow.…”
Section: Introductionmentioning
confidence: 99%